Standar Discharge Planning terhadap Keterampilan Ibu Primipara dalam Memandikan Bayi Baru Lahir - Riyan Dwi Prasetyawan; Ahmad Rosuli; Badrul Munif (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of standardized discharge planning on the skills of mothers who have just given birth to their first child in bathing their newborns. The type of research used is quantitative research using a pre-experimental design, one group pretest-posttest design, with a sample of 30 respondents who were given standard discharge planning treatment. The results showed that there was a significant difference between the average score of respondents' skills before and after treatment with a difference of -2.6 and p-value = 0.001. In conclusion, the provision of standard discharge planning can improve the skills of mothers in bathing newborns. Keywords: Discharge Planning, Skills, Baby Bathing, Primipara, Standard